2009
DOI: 10.1007/s10734-009-9200-6
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduates’ learning experience and learning process: quantitative evidence from the East

Abstract: This article examines the construct validity of the Course Experience Questionnaire (CEQ) in Hong Kong and investigates the similarities and differences in the process of learning among students in different disciplinary studies. It is based on a survey of 1,563 undergraduate students in two disciplines, humanities and sciences, and of principally Chinese ethnicity. Findings from exploratory and confirmatory factor analyses support the scale structure of the four subscales of a modified version of the CEQ (goo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
1
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 39 publications
2
48
1
9
Order By: Relevance
“…This result coincides with other research studies (Ginns & Ellis, 2007;Lizzio, Wilson, & Simons, 2002). Various authors (Watkins, 1983;Ginns & Ellis, 2007;Webster, Chan, Prosser & Watkins, 2009) have suggested that when students have positive perceptions of the learning environment, they tend to use a deeper learning approach and demonstrate higher academic achievement. It should be noted that the blended learning model should include a significant amount of independent work, and students' success depends on their self-management skills and their positive perceptions of the learning environment (Reisetter, Lapointe & Korcuska, 2007).…”
Section: Discussionsupporting
confidence: 90%
“…This result coincides with other research studies (Ginns & Ellis, 2007;Lizzio, Wilson, & Simons, 2002). Various authors (Watkins, 1983;Ginns & Ellis, 2007;Webster, Chan, Prosser & Watkins, 2009) have suggested that when students have positive perceptions of the learning environment, they tend to use a deeper learning approach and demonstrate higher academic achievement. It should be noted that the blended learning model should include a significant amount of independent work, and students' success depends on their self-management skills and their positive perceptions of the learning environment (Reisetter, Lapointe & Korcuska, 2007).…”
Section: Discussionsupporting
confidence: 90%
“…It confirmed that deep learners have a positive attitude toward those teaching aids which let them have advanced academic achievement [12]. As Webster [41] proposed, a positive learning environment could facilitate students to adopt a deep learning approach.…”
Section: Implications For the Teaching And Learning And Conclusionmentioning
confidence: 78%
“…Una característica interesante del modelo 3P es que plantea que los aprendizajes que alcanzan los estudiantes responden a cómo perciben algunos elementos del contexto concreto en el que se encuentran, como la buena docencia, las metas y objetivos claros, la evaluación apropiada o la carga de trabajo apropiada, entre otros (Ginns & Ellis, 2009;Webster, Chan, Prosser & Watkins, 2009). Más específicamente, la investigación revela que la percepción de buena docencia y metas y objetivos claros presentan correlaciones directas con el uso de un enfoque profundo de aprendizaje, a diferencia de la percepción sobre la carga académica de trabajo y la evaluación, que presentan correlaciones con el aprendizaje superficial (Ramsden, 2003).…”
Section: Abstract: Validation Reliability Spq Ceq Chileunclassified
“…Para ejecutar el proceso de adaptación de los instrumentos, se consideraron las versiones en inglés utilizadas por Webster et al (2009) y Biggs, Kember y Leung (2001 del SPQ y el CEQ, respectivamente, y se contrastaron con las versiones traducidas y adaptadas al contexto chileno por González et al (2011).…”
Section: Instrumentosunclassified